Relaparotomy in general surgery department of tertiary care hospital of Western India - Patel, Hemil; Patel, Piyush; Shah, D. K. (International Surgery Journal, 2016)
Background:Relaparotomy has to be performed in case of certain post-operative complications. Incidence of relaparotomy differs according to hospital setup as well as patient characteristics and initial surgery. It also depends on post-operative care given to patient following first surgery and incidence of post-operative sepsis. This study was carried out to know the incidence of relaparotomy and indications of it, so that in the future this factors can be modified and incidence can be further lowered. Methods: This is an observational study in which 75 relaparotomy cases reported during the period of May 2008 to September 2010 were included. All patients irrespective of age and sex, who have undergone re exploration of the abdomen during the period of hospitalization after the first operation and discharge of patients. All the gynaecological and obstetrical laparotomies were excluded. Data were recorded in pre-validated case record form. Results:Incidence of relaparotomy was 2.84%. It was most common in age group of 31 to 40 years; with mean age of 39.25 years. The most common indication of relaparotomy was leak (34 patients); from an anastomotic site (29 patients) or from perforation (5 patients). The mean duration between first Laparotomy and relaparotomy was 6.85 days. The mortality was 34.72% (25 patients). Mean number of days stay in ICU or the patient requires continuous close monitoring was 4.01 days; mean days of hospitalization was 25.72 days. Conclusions:Relaparotomy is lifesaving procedure for patients. Incidence of relaparotomy depends on expertise in primary surgery, proper surgical technique and prevention of post-operative infection.